Thermodynamic description of Be(II) solubility and hydrolysis in acidic to hyperalkaline NaCl and KCl solutions. (June 2020) - Çevirim-Papaioannou, Neşe; Gaona, Xavier; Böttle, Melanie; Bethune, Ezgi Yalçıntaş; Schild, Dieter; Adam, Christian; Sittel, Thomas; Altmaier, Marcus
Abstract: The solubility of Be(II) is investigated in carbonate-free dilute to concentrated HCl–NaCl–NaOH, KCl–KOH, NaOH and KOH solutions. Undersaturation experiments were performed under Ar atmosphere at T = (22 ± 2) °C. XRD, XPS, SEM and quantitative chemical analysis confirm that α-Be(OH)2 (cr) is the solid phase controlling the solubility in all evaluated systems. No transformation of α-Be(OH)2 (cr) to β-Be(OH)2 (cr) or ternary solid phases Na/K–Be(II)–OH(s) is observed in the investigated systems within the timeframe of this study ( t  ≤ 600 days). An amphoteric solubility behaviour of Be(II) is observed with a solubility minimum at pHm  ≈ 9.5 (with [Be(II)] ≈ 10 −6.8  M), regardless of the ionic strength. The combination of solubility data determined in acidic pHm conditions and the hydrolysis scheme reported in the literature for cationic hydrolysis species of Be(II) is used for the determination of the solubility constant of α-Be(OH)2 (cr), log * K °s, 0 = (6.9 ± 0.4). Slope analysis of the solubility data in alkaline to hyperalkaline conditions and 9 Be NMR support the predominance of the monomeric hydrolysis species Be(OH)2 (aq), Be(OH)3 – and Be(OH)4 2− within the strongly alkaline pHm -conditions relevant in cementitious systems. The comprehensive solubility dataset collected within this study in combination with extensive solid and aqueous phase characterization allow the development of a complete chemical, thermodynamic and (SIT) activity model for the system Be 2+ –Na + –K + –H + –Cl – –OH – –H2 O(l). This model provides an accurate and robust tool for the evaluation of Be(II) solubility and speciation in a diversity of geochemical conditions, including source term calculations of beryllium in the context of the nuclear waste disposal Safety Case. Highlights: Systematic solubility and spectroscopic study with Be(II) in NaCl and KCl systems. α-Be(OH)2 (cr) controls the solubility of Be(II) in the investigated systems. Comprehensive thermodynamic, chemical and SIT activity models derived. Accurate description of the system Be 2+ –Na + –K + –H + –Cl – –OH – –H2 O(l) provided. Be(OH)3 – and Be(OH)4 2− confirmed as relevant species in cementitious systems.